Italy in the Eurozone - Christian Keuschnigg; Linda Kirschner; Michael Kogler; Hannah Winterberg (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Using a DSGE model with nominal wage rigidity, we investigate two scenarios for the Italian economy. The first considers sustained policy commitment to reform. The results indicate the possibility of `growing out of bad initial conditions', if fiscal consolidation is combined with a program for bank recovery and for competitiveness and growth. The second scenario involves a strong asymmetric recession. It is likely to be very severe under the restrictions of the currency union. A benign exit from the Eurozone with stable investor expectations could substantially dampen the short-run impact. Stabilization is achieved by monetary expansion, combined with exchange rate depreciation. However, investor panic may lead to escalation. Capital market reactions would offset the benefits of monetary autonomy and much delay the recovery.
Keywords: E42; E44; E60; F30; F36; F45; G15; G21; 330; Italy; competitiveness; sovereign debt; bad loans; bank recapitalization; European crisis